ANALISIS MUSLIM FRIENDLY TOURISM, LIVING COST, CULTURE DAN KURS VALUTA ASING TERHADAP MINAT WISATAWAN MUSLIM DALAM PENGAMBILAN KEPUTUSAN UNTUK BERKUNJUNG KE JEPANG - Gibtiah, Gibtiah; Desiana, Lidia; Aryanti, Aryanti (Universitas Islam Negeri Raden Fatah Palembang, 2018)
The purpose of this research is to determine the influence of Muslim Friendly Tourism, Living Cost, Culture And Foreign Exchange to Interest of Muslim Tourists in Decision Making To Visit Japan. Sampling method was 120 respondents using purposive sampling method. Method of data analysis using Structural Equation Modeling (SEM) Method. The result of the analysis shows that the three variables that have positive influence. The variables of Muslim friendly tourism, culture and foreign exchange rate have an indirect positive effect on Muslim tourist decision through the change of interest to visit Japan. While the variable of living cost, negatively influence indirectly to decision of Muslim tourists through change of interest to visit to Japan.